Complete Low‐Temperature Transformation and Dissolution of the Three Main Components in Corn Straw. Issue 2 (1st February 2023) - Qin, Diyan; Liu, Yancheng; Yang, Ruofeng; Li, Jianmei; Hu, Changwei
Abstract: The conversion of biomass faces the challenge of mass and heat transfer, as well as the exertion of heterogeneous catalyst, because raw biomass exists usually in solid state. In this work, the simultaneous transformation and dissolution of the three main components (hemicellulose, cellulose, lignin) in corn straw were achieved in ethanol/ valerolactone (GVL)/H2 O (10 : 10 : 40, v / v / v ) co‐solvent system. With the assistance of AlCl3  ⋅ 6H2 O, the conversion of hemicellulose, lignin and cellulose was >96 % at 170 °C. The conversion of solid biomass into fluid, overcoming the mass transfer restrictions between solid biomass and solid catalysts, provides new raw materials to further upgrading. H2 O could penetrate inside the crystalline cellulose to swell even dissolve it, while ethanol and GVL acted as media to dissolve especially the G unit in lignin. The H + derived from AlCl3  ⋅ 6H2 O hydrolysis could break the linkages of lignin‐hemicellulose and glycosidic bond in saccharides, and aluminum chloride promoted the next degradation of polysaccharides to small molecules. Consequently, as high as 33.2 % yield of levulinic acid and 42.2 % yield of furfural were obtained. The cleavage of β‐O‐4 and Cβ −Cγ bonds in lignin produced large amounts of lignin‐derived dimers and trimers. The total yield of monomeric phenols is up to 8 %. Abstract : The complete conversion technology of biomass developed in this paper transforms all the three components of solid biomass into fluids, not only obtaining the desired yield of small molecules, but also providing a favorable raw material for the subsequent upgrading, promoting heat and mass transfer, and facile separation of catalyst.